2020
DOI: 10.1108/ijopm-05-2019-0339
|View full text |Cite
|
Sign up to set email alerts
|

Inventory and ordering decisions: a systematic review on research driven through behavioral experiments

Abstract: PurposeThe success of a supply chain is highly reliant on effective inventory and ordering decisions. This paper systematically reviews and analyzes the literature on inventory ordering decisions conducted using behavioral experiments to inform the state-of-the-art.Design/methodology/approachThis paper presents the first systematic review of this literature. We systematically identify a body of 101 papers from an initial pool of over 12,000.FindingsExtant literature and industry observations posit that decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 174 publications
(325 reference statements)
0
52
0
3
Order By: Relevance
“… Method-based reviews are dedicated to analyzing the utilization of a specific method in a subject area. Examples of method-based reviews include the use of structural equation modeling in marketing ( Hair, Hult, Ringle, Sarstedt, & Thiele, 2017 ), the use of qualitative case research in international entrepreneurship ( Ji, Plakoyiannaki, Dimitratos, & Chen, 2019 ), and the use of behavioral experiments in operations and production management ( Perera, Fahimnia, & Tokar, 2020 ). Meta-analytical reviews are focused on statistical assessments of prior empirical research on a specific research topic, whereby the common effects are identified through consistency in the direction of effect, effect size, and statistical power, and the reason for variations are explained.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… Method-based reviews are dedicated to analyzing the utilization of a specific method in a subject area. Examples of method-based reviews include the use of structural equation modeling in marketing ( Hair, Hult, Ringle, Sarstedt, & Thiele, 2017 ), the use of qualitative case research in international entrepreneurship ( Ji, Plakoyiannaki, Dimitratos, & Chen, 2019 ), and the use of behavioral experiments in operations and production management ( Perera, Fahimnia, & Tokar, 2020 ). Meta-analytical reviews are focused on statistical assessments of prior empirical research on a specific research topic, whereby the common effects are identified through consistency in the direction of effect, effect size, and statistical power, and the reason for variations are explained.…”
Section: Methodsmentioning
confidence: 99%
“…Method-based reviews are dedicated to analyzing the utilization of a specific method in a subject area. Examples of method-based reviews include the use of structural equation modeling in marketing ( Hair, Hult, Ringle, Sarstedt, & Thiele, 2017 ), the use of qualitative case research in international entrepreneurship ( Ji, Plakoyiannaki, Dimitratos, & Chen, 2019 ), and the use of behavioral experiments in operations and production management ( Perera, Fahimnia, & Tokar, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent advances in decision making research using simulations of the Beer Game task have shown that coordination risk (the risk that individuals' decisions contribute to a collective outcome but the decision rules followed by each individual are not certain) which contributes to the bullwhip effect can be mitigated with coordination stock (holding additional on-hand inventory) but that the behavioral causes of the supply chain instability are robust [68,[79][80][81]. Sterman and Dogan [69] show that because of this persistence of instability, individuals are likely to seek larger safety stocks (hoarding) or order more than what is demanded of them (phantom ordering).…”
Section: Environmental and Contextual Characteristicsmentioning
confidence: 99%